Mandibular Advancement Devices’ Efficacy in Treating Obstructive Sleep Apnea - An Overview of Clinical Data - Maideen, Naina Mohamed Pakkir; Nabi, Rumisa; Sirajudeen, Mohamed Nazar; Mohamed, Azmina Parveen Raja (Current Respiratory Medicine Reviews, 2025)
BackgroundComplete or partial collapse of the upper airway for a few seconds during sleep is the cause of obstructive sleep apnea (OSA). OSA affects about half of the world's population. Although there are numerous treatment options for OSA, continuous positive airway pressure (CPAP), mandibular advancement device (MAD), and surgeries are regarded as mainstream therapies.ObjectiveSince MAD is a better alternative to CPAP for patients who are unwilling to utilize CPAP therapy or who do not comply with it, our current review focuses on how effective MAD is at managing OSA.MethodsTo find publications relevant to the safety and effectiveness of MAD in the treatment of OSA, online databases such as Medline/PubMed/PMC, Scopus, Web of Science, Google Scholar, and reference lists were searched.ResultsThrough the reduction of apnea-hypopnea index (AHI), snoring, and improved sleep quality, a number of prospective and retrospective observational studies, randomized controlled clinical trials and meta-analyses showed that MADs are beneficial for patients with mild-to-moderate OSA and snoring. Although CPAP therapy is the gold standard for treating OSA, patients who cannot or do not want to utilize CPAP therapy may benefit from MAD therapy as an alternative or as a supplementary treatment. For patients with OSA, the use of oral appliances, including MAD, is advised by the American Academy of Sleep Medicine (AASM), American Academy of Dental Sleep Medicine (AADSM), and National Institute of Clinical Excellence (NICE) guidelines.ConclusionNumerous randomized controlled clinical trials, prospective and retrospective observational studies, and meta-analyses have demonstrated that MADs are beneficial in treating OSA patients by reducing snoring, enhancing sleep quality, and lowering the apnea-hypopnea index (AHI). A licensed dentist should utilize a custom, titratable MAD when a sleep physician prescribes oral appliance therapy for an adult patient with OSA. The patients managed with MAD therapy should be advised to pay follow-up visits.
Keywords: Obstructive sleep apnea